The Executive Power of the Acte Van Dading in Mediation of Child Custody Disputes at the West Nusa Tenggara Religious Court - Ahmad Syauqy Alfan; Miftahul Huda; Teti Indrawati Purnamasari (Walidem Institute and Publishing, 2026)
Objective: This study aims to explain the legal review of various influencing factors and the urgency of implementing a Peace Deed in resolving child custody claims through mediation in Religious Courts, with a focus on court decisions in West Nusa Tenggara Province. Theoretical Framework: This study is grounded in normative legal theory, dispute resolution theory, and mediation theory, emphasizing the role of legal harmonization and judicial consistency in achieving justice, particularly in family law disputes involving child custody. Literature Review: Legal Framework of Mediation in Religious Courts, The Role of Peace Deeds in Dispute Resolution, Child Custody in Islamic Family Law, Judicial Consistency and Legal Certainty, and Harmonization of Laws and Regulations. Method: This study employs a qualitative approach through a literature review using a normative legal method, supported by statute, case, and conceptual approaches. Data collection was conducted through legal research. Primary legal materials include Article 130 HIR, Article 154 RBg, and PERMA No. 1 of 2016 concerning mediation procedures, while secondary data consist of relevant legal literature and scholarly works. Results: The findings reveal inconsistencies and disharmony between Article 130 HIR and Article 154 RBg with PERMA No. 1 of 2016 regarding the application of Peace Deeds in mediation processes. This lack of harmonization has resulted in overlapping and inconsistent judicial decisions, particularly in child custody cases decided by Religious Courts in several regions of West Nusa Tenggara Province. Implications: The study suggests the need for legal harmonization and clearer regulatory frameworks to ensure consistency in the application of mediation and Peace Deeds in Religious Courts, thereby enhancing legal certainty and protecting the best interests of the child. Novelty: This study offers a comprehensive legal analysis highlighting the urgency of harmonizing mediation regulations and strengthening the role of Peace Deeds in child custody dispute resolution within Religious Courts, particularly through the lens of case decisions in West Nusa Tenggara Province.